2010
DOI: 10.1210/jc.2009-2697
|View full text |Cite
|
Sign up to set email alerts
|

The Accuracy of the Glucagon Test Compared to the Insulin Tolerance Test in the Diagnosis of Adrenal Insufficiency in Young Children with Growth Hormone Deficiency

Abstract: This study shows that glucagon is an accurate and safe diagnostic test for adrenal function in young children who are at risk for adrenal insufficiency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
0
7

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 42 publications
3
29
0
7
Order By: Relevance
“…In a recently reported study, GH therapy was even found to be associated with acute adrenal insufficiency and death [5]. Thus, assessment of the hypothalamic-pituitary-adrenal (HPA) axis at the time of evaluation for GH deficiency is often recommended [6,7,8]. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a recently reported study, GH therapy was even found to be associated with acute adrenal insufficiency and death [5]. Thus, assessment of the hypothalamic-pituitary-adrenal (HPA) axis at the time of evaluation for GH deficiency is often recommended [6,7,8]. …”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, water may be given freely during the test. Thus, in our institute as well as other pediatric centers [7,13], this test has become much more popular in recent years, especially for use in children. Despite the frequency with which the GST is carried out in children, to date there have been few pediatric studies designed to evaluate the accuracy and specificity of the test in assessing the HPA axis in children.…”
Section: Introductionmentioning
confidence: 99%
“…In agreement, we used ITT to evaluate the HPA axis in GHD children. Although we showed good correlation between morning serum cortisol and its peak during ITT, it is widely demonstrated that the baseline morning serum cortisol concentration has limited predictive power in differentiating between normal and impaired HPA function [27,28,34]. In agreement with these observations, our data showed that morning cortisol evaluation cannot be considered a reliable indicator of AI in children with GHD because the capacity of morning cortisol to diagnose AI differs from that of the cortisol peak during ITT; that is to say, with the cortisol peak we can diagnose a percentage of potential AI that cannot be diagnosed with morning cortisol.…”
Section: Discussionmentioning
confidence: 66%
“…They suggested cortisol cutoff of 16 µg/dL for best pair of sensitivity and specificity (20). Another cortisol cutoff was suggested at 14.6 compared to 20 µg/dL for ITT (21).…”
Section: Dynamic Testing Of Hpa Axismentioning
confidence: 99%